2023
DOI: 10.1111/jpn.13875
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of glucolipid metabolism and oxidative stress in breeding pigeons (Columba livia) during lactation

Jie Peng,
Weiying Huang,
Menglin Yang
et al.

Abstract: Breeding pigeons is a fundamental source of profit in various enterprises but little is known on the metabolic laws governing their lactation. In this study, we analysed the metabolic profile of different sex of breeding pigeons (Columba livia, European pigeons, Mimas) during lactation. We found that male pigeons exhibited catabolism during lactation. Extension of lactation resulted in increased weight loss, then slow recovery of body weight. Conversely, the weight loss in female pigeons peaked on the seventh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Unlike mammals, both male and female pigeons produce pigeon crop milk [ 18 ], but they exhibit differences in lactation initiation times and durations. Actually, previous studies have demonstrated distinct metabolic characteristics during lactation between male and female pigeons [ 19 ], suggesting different mechanisms of milk production. Although previous studies have mainly focused on the formation mechanisms of pigeon crop milk, the chemical composition of pigeon crop milk and the underlying mechanisms affecting its production between male and female pigeons remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike mammals, both male and female pigeons produce pigeon crop milk [ 18 ], but they exhibit differences in lactation initiation times and durations. Actually, previous studies have demonstrated distinct metabolic characteristics during lactation between male and female pigeons [ 19 ], suggesting different mechanisms of milk production. Although previous studies have mainly focused on the formation mechanisms of pigeon crop milk, the chemical composition of pigeon crop milk and the underlying mechanisms affecting its production between male and female pigeons remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%